Application of the Two Stay Two Stray Model to Increase Student Interest in Hajj and Umrah Worship Materials - Wawar Kurniasih; Wina Paul (GoAcademica Research & Publishing, 2022)
The background of this research is empirical data showing that the learning outcomes of class IX-C students of SMP Negeri 1 Gekborn Cianjur in the Hajj and Umrah services have not yet achieved optimal results, which are still below the Minimum Completeness Criteria (KKM) which is determined at 70. The average score achieved by students regarding socio-cultural change and globalization is 62, with 52% learning completeness. At the time of learning, students were less active in asking questions, collaborating, expressing opinions, or answering questions. In connection with this, it is necessary to increase learning about socio-cultural changes and globalization, and one of them is by using a suitable learning model. This study aims to determine the increase in students’ interest in learning by using a cooperative model of the Two Stay Two Stray type in class IX-C of SMPN 1 Gekbrong Cianjur. The method used in this research is Classroom Action Research, and data collection techniques are tests, observations, and interviews. The research subjects were 35 students of class IX-C. The data processing technique was carried out quantitatively on a hundred scale. The results showed that the average learning activity in the first cycle was 75.24, and in the second cycle was 82.86. In the first cycle, student learning outcomes about Hajj and Umrah reached an average of 74, with learning completeness at 68.57%, and the second cycle reached an average of 83.71, with learning completeness reaching 100%. The study results concluded that using the Two Stay Two Stray type of cooperative model could increase student interest in Hajj and Umrah in class IX-C of SMP Negeri 1 Gekbrong Cianjur.